Validation of Addenbrooke’s cognitive examination III for detecting mild cognitive impairment and dementia in Japan - Takenoshita, Shintaro (BMC Geriatr, 2019)
BACKGROUND: Early detection of mild cognitive impairment (MCI) and dementia is very important to begin appropriate treatment promptly and to prevent disease exacerbation. We investigated the screening accuracy of the Japanese version of Addenbrooke’s Cognitive Examination III (ACE-III) to diagnose MCI and dementia. METHODS: The original ACE-III was translated and adapted to Japanese. It was then administered to a Japanese population. The Hasegawa Dementia Scale-revised (HDS-R) and Mini-mental State Examination (MMSE) were also applied to evaluate cognitive dysfunction. In total, 389 subjects (dementia = 178, MCI = 137, controls = 73) took part in our study. RESULTS: The optimal ACE-III cut-off scores to detect MCI and dementia were 88/89 (sensitivity 0.77, specificity 0.92) and 75/76 (sensitivity 0.82, specificity 0.90), respectively. ACE-III was superior to HDS-R and MMSE in the detection of MCI or dementia. The internal consistency, test-retest reliability, and inter-rater reliability of ACE-III were excellent. CONCLUSIONS: ACE-III is a useful cognitive test to detect MCI and dementia. ACE-III may be widely useful in clinical practice.